If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(6) + 9 * 5 + -5 = 0 Multiply 4 * 6 24 + 9 * 5 + -5 = 0 Multiply 9 * 5 24 + 45 + -5 = 0 Combine like terms: 24 + 45 = 69 69 + -5 = 0 Combine like terms: 69 + -5 = 64 64 = 0 Solving 64 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -3p+15p=-12 | | 42(55+36)= | | (10v^4-2v^2+6v^3-7)-(9-v+2v^4)= | | 11s+-7s+-2s+-2=18 | | 1*4+(10-9)*3= | | 12(95+17)= | | 8h+-1h+-16h=-9 | | 2*3+2(15-7)+7= | | 31(3+8)= | | 4b+-2b+10=4 | | 5x^3-125x=0 | | 8(450+200)= | | -5c+-1c+1=13 | | 2*3+3(11-5)+7= | | 12(10+15)= | | -5c+-1c+-1=13 | | -2(-3-4y)=10 | | 3+5x=-6 | | 3(5+7)= | | 1v+5v=12 | | 8(4+9)= | | 6n+-14n+6n+-1=-15 | | (7q-3q^3)+(16-8q^3+5q^2-q)= | | 6n+-14n+6n+-1=15 | | 5(2+4)= | | -25x^2=100 | | 8h+-7h+3h=16 | | (6m^3-5)-(m^3+4m^2-9m-2)= | | -2x-8=3 | | 6h+-11h=-15 | | 36=3(-2x) | | -6(2h+8)+7= |